Detection of formaldehyde. - Abu Bakar, Fatimah; Marzuki, Nur Indang; Salleh, Abu Bakar; Yusof, Nor Azah; Lee, Yook Heng (2010)

(untitled)
The presence invention discloses an electrochemical method to determine the presence of formaldehyde in food sample, for example fish and other seafood products by way of an enzymatic-based sensor, which comprises an electrode coated with an immobilized enzyme and measuring the current changes as the output signal at a constant voltage, which indicates the presence of formaldehyde in the sample.